Light-Responsive Block Copolymers - Schumers, Jean-Marc; Fustin, Charles-André; Gohy, Jean-François (Macromolecular rapid communications., 2010)
Stimuli‐responsive polymers are the subject of intense research because they are able to show responses to various environmental changes. Among those stimuli, light has attracted much attention since it can be localized in time and space and it can also be triggered from outside of the system. In this paper, we review light‐responsive block copolymers (LRBCs) that combine characteristic features of block copolymers, e.g., self‐assembly behavior, and light‐responsive systems. The different photo‐responsive moieties that have been incorporated so far in block copolymers as well as the proposed applications are discussed. Light‐responsive block copolymers are reviewed. The different photo‐responsive moieties that have been incorporated so far in block copolymers as well as the proposed applications are discussed both in solution and in bulk.